ASSESSMENT OF HEALTH-RELATED QUALITY OF LIFE IN CHRONIC HEPATITIS B INFECTION PATIENTS IN TURKEY: A MULTICENTER STUDY - Karacaer, Z.; Cakir, B.; Erdem, H.; Ugurlu, K.; Durmus, G.; Ince, N. K.; Boluktas, R. P. (Elsevier Science Bv, 2016)
[Abstract Not Available]
EASL International Liver Congress -- APR 13-17, 2016 -- Barcelona, SPAIN